Bacterial community of sediments under the Eastern Boundary Current System shows high microdiversity and a latitudinal spatial pattern - Fonseca, Alexis; Espinoza, Carola; Nielsen, Lars Peter; Marshall, Ian P. G.; Gallardo, Victor A. (Frontiers in Microbiology, 2022)
The sediments under the Oxygen Minimum Zone of the Eastern Boundary Current System along central-south Peru and north-central Chile, known as Humboldt Sulfuretum (HS), is an organic-matter-rich benthic habitat, where bacteria process a variety of sulfur compounds under low dissolved-oxygen concentrations, and high sulfide and nitrate levels. This study addressed the structure, diversity and spatial distribution patterns of the HS bacterial community along northern and south-central Chile using 16S rRNA gene amplicon sequencing. The results show that during the field study period, the community was dominated by sulfur-associated bacteria. Indeed, the most abundant phylum was Desulfobacterota, while Sva0081 sedimentary group, of the family Desulfosarcinaceae (the most abundant family), which includes sulfate-reducer and H2 scavenger bacteria, was the most abundant genus. Furthermore, a spatial pattern was unveiled along the study area to which the family Desulfobulbaceae contributed the most to the spatial variance, which encompasses 42 uncharacterized amplicon sequence variants (ASVs), three assigned to Ca. Electrothrix and two to Desulfobulbus. Moreover, a very high microdiversity was found, since only 3.7% of the ASVs were shared among localities, reflecting a highly diverse and mature community.